ETHNOBOTANICAL SURVEY OF PHOENIX DACTYLIFERA L. POLLEN USED FOR THE TREATMENT OF INFERTILITY PROBLEMS IN ALGERIAN OASES - Selmani, Cherifa; Chabane, Djamila; Bouguedoura, Nadia (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The Phoenix dactylifera L. (date palm) is known for its traditional medicinal properties across thehistory of native population in Algerian Sahara. There is a large trend of consumption of date palm pollen preparationsin many human infertility cases in our country. However, the validity has not been scientifically tested. There has beenno direct scientific research on this application. This study was undertaken to identify cultivars with greater potential inthe traditional medicine uses. To evaluate the effects of da palm pollen on some sexual behavioural parameters of maleadult rats, we tested the role of pollen powder from Deglet Nour cultivar on some male reproductive parameters.Materials and Methods: An Ethnobotanical survey was conducted in 17 oases in southern Algeria to identify allcultivars with medicinal interest. Local people were interviewed with open questions. A questionnaire and personalinterviews for data collection were designed to record important cultivars, parts used and preparations. To determinethe active constituents of date palm pollen used in traditional medicine, a phytochemical screening was performed. Theeffects of oral administration of date palm pollen suspension on male adult rats were investigated on body and testicleweights, serum testosterone level.Results: 131 prominent cultivars were found within 12 cultivars containing various parts with medicinal effects. Someprimary and secondary metabolites were detected by phytochemical screening. The pollen increased the weight of thebody, testicles and enhanced the serum testosterone level of male rats treated.Conclusion: The present survey has provided the identification and recognition of date palm cultivars used intraditional Saharan medicine. Date palm pollen could improve sexual activities in male infertility cases and may beattempted to derive drugs.